The Use of Soekarno Films as A Learning Resource for History Class XI IPS 3 at State Senior Secondary School 11 Pontianak - Dianisty, Rizky Ananda; Firmansyah, Andang; Putri, Astrini Eka (Universitas Tanjungpura, 2025)
This study describes the use of Soekarno film media as a history learning resource for Class XI IPS 3 State High School 11 Pontianak. This study is descriptive qualitative. This study uses class XI IPS 3 instructors and students as informants. This research collected data by observation, interview, and documentation. This study reduces, presents, and draws inferences from data. Triangulation and source triangulation are employed for data veracity. This research found: (1) To adapt Soekarno cinema medium to history learning, instructors must construct a learning implementation plan (RPP). (2) History education using Soekarno cinema medium. (3) Technical and non-technical challenges remain in using Soekarno film medium for history study.